ChatGPT as a support tool in the teaching of Mathematics - Santos, Renan Pereira (2023)
This article discusses the use of the ChatGPT application in Mathematics Education. The conversational model of artificial intelligence answers users' questions autonomously, based on internet data and with the ability to solve mathematical questions, prepare lesson plans, write dissertation texts, create poetry and songs, for example. With this, we intend to investigate the benefits and possible harms of this resource in the teaching and learning processes of Mathematics. To this end, based on the study and research trajectory of the Study Group in Mathematics Education (GEEM), we approach the language in which ChatGPT is inserted from the available bibliographic reference and present some of the possibilities that this innovative resource offers and that can, evidently be explored in Mathematics classes and by students and teachers.